2006
DOI: 10.1121/1.2221552
|View full text |Cite
|
Sign up to set email alerts
|

An experimental evaluation of regular polyhedron loudspeakers as omnidirectional sources of sound

Abstract: Multiple-driver dodecahedron loudspeakers are commonly used in room acoustics measurements as omnidirectional sources of sound. Yet they and other regular polyhedron loudspeakers become "multidirectional" above their omnidirectional cutoff frequencies ͑often near 1 kHz͒. Because these cutoff frequencies normally fall within common measurement bandwidths, one might question whether anything is really extraordinary about the dodecahedron loudspeaker or whether another regular polyhedron geometry would actually p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 5 publications
0
38
0
1
Order By: Relevance
“…[4][5][6][7]. More recently, spherical arrays with independently controlled transducers were used as sources featuring adjustable directivity [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7]. More recently, spherical arrays with independently controlled transducers were used as sources featuring adjustable directivity [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, with the spherical loudspeaker (upper box, solid line), the floor reflection in the deconvolved response is hard to detect due to interference with reflections produced by the different driver elements in the array. 1 Furthermore the amplitude of the ceiling reflection is reduced due to ceiling absorption when compared to the floor reflection amplitude in the LIB room response. The reflection produced by the loudspeaker above the LIB position is also noticeable (ceiling LS in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, spherical loudspeakers are typically assumed to be point-like, although they are directional at high frequencies and have considerable size. 1,2 Electrical sparks are small, but they are not repeatable and feature directional radiation patterns. 3 A potential candidate for an omnidirectional and repeatable acoustic point source with sufficient sound pressure is the laser-induced air breakdown, LIB.…”
Section: Introductionmentioning
confidence: 99%
“…A tetrahedron sound source with three small loudspeakers (one on each side except in the base which lay on the floor) was used as an approximation of an omnidirectional source. In fact, as demonstrated by Leishman, Rollins, and Smith (2006), despite this regular polyhedron having a low cutoff frequency, which according to the physical dimensions is 166 Hz (full scale), it shows the most uniform radiation above that limit. Measurements along the horizontal plane in free field conditions showed that small variations (within ±1.5 dB) in the level appeared at 250 and 500 Hz octaves (full scale), while at 125 Hz and 1 kHz, variations were greater (within ±3.5 dB).…”
Section: Measurements Of Room Acoustic Parametersmentioning
confidence: 91%